Probing the assembly of transcription initiation complexes through changes in σ(N )protease sensitivity - Casaz, Paul (The National Academy of Sciences of the USA, 1997)
The alternative bacterial σ(N) RNA polymerase holoenzyme binds promoters as a transcriptionally inactive complex that is activated by enhancer-binding proteins. Little is known about how sigma factors respond to their ligands or how the responses lead to transcription. To examine the liganded state of σ(N), the assembly of end-labeled Klebsiella pneumoniae σ(N) into holoenzyme, closed promoter complexes, and initiated transcription complexes was analyzed by enzymatic protein footprinting. V8 protease-sensitive sites in free σ(N) were identified in the acidic region II and bordering or within the minimal DNA binding domain. Interaction with core RNA polymerase prevented cleavage at noncontiguous sites in region II and at some DNA binding domain sites, probably resulting from conformational changes. Formation of closed complexes resulted in further protections within the DNA binding domain, suggesting close contact to promoter DNA. Interestingly, residue E36 becomes sensitive to proteolysis in initiated transcription complexes, indicating a conformational change in holoenzyme during initiation. Residue E36 is located adjacent to an element involved in nucleating strand separation and in inhibiting polymerase activity in the absence of activation. The sensitivity of E36 may reflect one or both of these functions. Changing patterns of protease sensitivity strongly indicate that σ(N) can adjust conformation upon interaction with ligands, a property likely important in the dynamics of the protein during transcription initiation.